Interference of a short-term exposure to nitrogen dioxide with allergic airways responses to allergenic challenges in BALB/c mice. Issue 4 (2002) - Proust, Barbara; Lacroix, Ghislaine; Robidel, Franck; Marliere, Maryse; Lecomte, Anthony; Vargaftig, B. Boris
Abstract : Nitrogen dioxide (NO2 ) is a common indoor and outdoor air pollutant whose role in the induction of asthma is unclear. We investigated the effects of NO2 on the development of asthma-like responses to allergenic challenge in BALB/c mice. Ovalbumin (OVA)-immunized mice were intranasally challenged with OVA or saline solution just before starting a 3 h exposure to 5 or 20 ppm NO2 or air. Twenty parts per million of NO2 induced a significant increase of bronchopulmonary hyperreactivity in OVA-challenged mice and of permeability according to the fibronectin content of the bronchoalveolar lavage fluid (BALF) 24 h after exposure, as compared with air or 5 ppm NO2 . Eosinophilia (cell counts in the BALF and eosinophil peroxidase of lung tissue) was detected at 24 and 72 h with similar levels for air and 20 ppm NO2, whereas a marked reduction was unexpectedly observed for 5 ppm NO2 . At 24 h, interleukin-5 in the BALF was markedly reduced at 5 ppm compared with 20 ppm NO2 and was also more intense for 20 ppm NO2 than for the air group. In contrast to specific IgG1 titers, anti-OVA IgE titers and interleukin-4 in the BALF were not affected by NO2 exposure. Irrespective of the concentration of NO2, OVA-challenged mice did not develop late mucosal metaplasia compared with those exposed to OVA-air. These results indicate that a short exposure to NO2 can exacerbate or inhibit some features of the development of allergic disease in mice and may depend on the concentration of pollutant.